Dissecting the shared genetic architecture between Alzheimer’s disease and frailty: a cross-trait meta-analyses of genome-wide association studies - Enduru, Nitesh; Fernandes, Brisa S.; Zhao, Zhongming (Frontiers in Genetics, 2024)
Frailty is the most common comorbidity medical condition affecting the aging population, and its prevalence increases in the population aged 65 or more. Frailty is commonly diagnosed using the frailty index (FI) or frailty phenotype (FP) assessments. Observational studies have indicated the presence and association of frailty with Alzheimer's disease (AD) individuals. However, the shared genetic and biological mechanism of these comorbidity has not been studied. To assess the genetic relationship between AD and frailty, we examined it at single nucleotide polymorphism (SNP), gene, and pathway levels. Overall, 16 genome-wide significant loci (15 unique loci) (pmetaanalysis < 5 x 10 -8 ) and 22 genes (21 unique genes) were identified between AD and frailty using cross-trait meta-analysis. The 8 shared loci implicated 11 genes: